Analisis Makna â€œIiwake Suruâ€ Dan â€œBenkai Suruâ€ Dalam Website Surat Kabar Bahasa Jepang Asahi.Com - Felicia, Felicia (Bina Nusantara University, 2011)
Verbs, particles, adjectives and conjunctions need to be understood well in learning Japanese.Â From a variety of verbs that exist, the author conducted an analysis of semantic field of the verbsÂ